Numerical simulation of Stephan blowing impacts on thermally laminated 3D flow of MHD trihybrid nanofluid with Soret and Dufour effects - Noureddine Elboughdiri; Munawar Abbas; Hamdi Ayed; Abir Mouldi; Nahid Fatima; Dilsora Abduvalieva; Mohamed Said; Ibrahim Mahariq; Ahmed S. Hendy; Ahmed M. Galal (Case Studies in Thermal Engineering)
The present work examines the Soret and Dufour significance on 3D flow of THNF (trihybrid nanofluid) over sheet with porous medium, heat radiation and Stephan blowing impacts using two different thermal conductivity models known as HCM (Hamilton-Crosser model) and YOM (Yamada-Ota model). A trihybrid nanofluid consisting of Cu, TiO2, Fe3O4 and propylene glycol (C3H8O2) as the base liquid is utilized. Performance-wise, this suggested model contrasts the two well-known thermal conductivity THNF models, the YOM (Yamada-Ota model) and the HCM (Hamilton-Crosser model). An advanced model for 3D analysis for THNF (trihybrid nanofluid) through Stefan blowing is existing in the Current investigation. This sophisticated study is essential to improving heat transfer efficiency in industrial processes involving intricate fluid flows under magnetic fields, such as nuclear reactor cooling systems, electronic device cooling systems, and aeronautical engineering. By accurately forecasting the behavior of nanofluids, the model aids in the optimization of thermal management in these systems, enhancing system dependability and energy efficiency. The mathematical results of governing comparisons remain acquired through shelling method (Bvp4c). The YOM and MCM models are used to describe how certain physical characteristics (concentration, velocity, and thermal) affect the usual profiles. The velocity profile and rate of heat transmission rise as the Stephan blowing parameter is increased, but the thermal distribution decreases. The Yamada-Ota model outperforms the Hamilton-Crosser thermal conductivity model of THNF in terms of heat transmission competence. The heat transfer rate is increased by 21.87 % for the ternary hybrid nanofluid, 16.56 % for the hybrid nanofluid, and 11.25 % for the mono nanofluid when the nanoparticles volume fraction is increased from 0.01 to 0.04.